FRI0329 Bone Erosive Damage in Systemic Lupus Erythematosus Is Associated with Local Hypervascularization Independently from ACPA Positivity. (15th July 2016) - Ceccarelli, F.; Perricone, C.; Cipriano, E.; Massaro, L.; Pendolino, M.; Capalbo, G.; Spinelli, F.R.; Alessandri, C.; Conti, F.; Valesini, G.
Abstract : Background: Joint involvement is one of the most frequent manifestations in patients affected by Systemic Lupus Erythematosus (SLE). It is characterized by a wide heterogeneity ranging from arthralgia to a severe erosive disease. The presence of local hypervascularization, evaluated by power Doppler (pD), is a well-established risk factor for the development of erosive damage in patients affected by Rheumatoid Arthritis (RA), together with the positivity for anti-citrullinated peptide antibodies (ACPA). To date, these data are not confirmed in SLE patients. Objectives: The aim of the present study was to estimate whether pD-evaluated local hypervascularization and the presence of ACPA represent risk factors for the development of erosive damage, assessed by ultrasonography, in SLE patients. Methods: One hundred two SLE patients with joint involvement were enrolled (M/F 1/101; mean age 44.5±11.6 years; mean disease duration 144.6±103.2 months). The ACPA presence was evaluated in 64 patients (ELISA, Euroimmun Italia, Italy). Ultrasonographic assessment of metacarpophalangeal (MCP), proximal interphalangeal (PIP) and metatarsophalangeal (MTP) was performed in all patients. The presence of pD and erosive damage were recorded by a dichotomic (present/absent) and a semiquantitative (0–3) score. A total score was obtained by the sum of modifications observed in every single joint. Results: Hypervascularization in at least one joint was identified in 25/102 (24.5%) patients (median score 4, range 1–23). This feature was more frequent at level of II and III MCP (12.7% and 8.8% respectively). Erosive damage was detected in 19 patients (18.7%). The presence of pD signal was significantly associated with the presence of erosive damage. Indeed, 13 pD-positive patients showed erosions (13/25, 52.1%) in at least one joint, compared with 6/77 (8.4%) pD-negative patients (median 1, range 0–9 vs median 0, range 0–7, P<0.0001). 21.8% of patients tested ACPA positive. However, there was no association between erosive damage and ACPA positivity. The erosive damage was reported in 21.4% of ACPA-positive patients and in 22.0% of ACPA-negative (P=NS). Conclusions: In the present study, we described for the first time the association between the presence of local hypervascularization, identified by pD ultrasonography, and erosive damage in a cohort of SLE patients with joint involvement. These results, similarly to RA, suggest the role of pD signal as a negative prognostic factor for erosive bone damage. This could help in the choice of a more aggressive therapeutic strategy. Conversely, the presence of ACPA does not seem to be associated with erosive damage, suggesting the presence of an alternative pathogenetic mechanism underlying the erosive damage in SLE patients. Disclosure of Interest: None declared